ANALISA PENERAPAN TPM (TOTAL PRODUCTIVE MAINTENANCE) DAN OEE (OVERALL EQUIPMENT EFFECTIVENESS) PADA MESIN AUTO CUTTING DI PT XYZ - Andyka Gumelar Ramadhani; Dea Zahra Azizah; Febri Nugraha; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
The research was conducted at PT XYZ company with two cutting machines as the object of research. In this study, the OEE value is influenced by unplanned factors and planned factors with an observation range starting from July 2021 to December 2021. The percentage value of the first cutting machine availability rate in December is 94.85% while the second cutting machine is 87 in August, 49%. Analysis of the performance rate of the first engine was in July with a percentage of 99.20% while the second engine was at a value of 98.45% in October. Then, for the highest quality rate value, the first machine was 99.96% in August while the second machine was in July at 99.89%. From the three analyzes, it can be concluded that the first engine has only one month of below-standard performance, while the second engine has several months of below-standard performance in accordance with the OEE value obtained on each engine.